OPTIMASI NIRA SAWIT DALAM PEMBUATAN MINUMAN SINBIOTIK DENGAN TAMBAHAN INULIN DAN KULTUR BAKTERI LACTOBACILLUS CASEI - Rinaldi, Wahyu; Raja, Pada Mulia; Syukri, Muhammad; Maharani, Rhyna; Rangkuti, Ika Ucha Pradifta (Institut Teknologi Sawit Indonesia (ITSI), 2022)
Oil palm trunks can produce quite a lot of sap water, which is approximately 10 per day for 1 month for 1 oil palm tree that is uprooted, currently, there is not much optimal processing of palm oil with an economical selling price, for this reason, it is necessary to develop functional foods. This study aims to determine whether palm sap can be used in the manufacture of symbiotic beverage products with optimum chemical, microbiological and organoleptic qualities. The study was arranged using a non-factorial Completely Randomized Design (CRD) method with 3 treatments of incubation time, namely 12 hours, 24 hours, and 36 hours with each treatment using 6 replications so that 18 experiments were carried out. The best treatment by SNI 2981:2009 was obtained at an incubation time of 24 hours, namely with a pH of 5.2, water content is 82.50%, total dissolved solids is 17.33%, the lactic acid content is 0.81%, a total lactic acid bacteria of 2.8 x 108 and produces a minimum dense texture with sufficient acidity. The organoleptic aspect of taste and aroma at 24 hours of incubation time was favored or acceptable to consumers with a taste score of 3.3b and aroma of 3.3ab (scale 1-5) in the hedonic rating test. Meanwhile, at 36 hours of incubation, consumers did not like it with a taste score of 2.2a and aroma of 2.1a. This is because the longer the fermentation time can increase the acidity of the product which causes the distinctive taste and aroma of palm sap to increase.